T6 MET targeted therapy in Lung adenocarcinoma: Does 'Resistant' EGFR make a MET-responsive dimer?. (12th November 2015) - Lee, RW; Ortiz-Zapater, E; Weitsman, G; Fruhwirth, G; Owen, W; Ng, T; Santis, G
Abstract : Introduction: Lung cancer has extremely poor survival with few effective treatments. Activating EGFR mutations (e.g. L858R), select for impressive EGFR tyrosine kinase inhibitor (TKI) responses but most develop resistance e.g. T790M mutations or MET amplification, which is thought to mediate EGFR-HER3 kinase switching. Preclinical studies suggest EGFR-MET TKI synergy and whilst phase III trials have failed, optimism remains for biomarker driven therapy. Hypothesis: EGFR-MET dimerisation determines MET TKI response. Objectives: Explore MET TKI responsiveness in EGFR mutant lung adenocarcinoma. Develop an EGFR-MET FLIM assay indicative of MET TKI responsiveness. Methods: An in vitro and murine xenograft model was derived from EGFR TKI resistant NCI-H1975 lung adenocarcinoma cells (L858R T790M). After shEGFR knockdown we re-expressed EGFR L858R or WT to represent three clinical scenarios: 1. H1975: 'EGFR-TKI Resistant' 2. H1975 L858R: 'EGFR Responders' or 3. H1975 WT (wildtype EGFR). Cells and xenografts (gavage) were challenged with exquisitely selective MET TKI, SGX523. Response was assessed by BrdU proliferation assays in vitro alongside random migration assays mimicking tumour cell motility. Xenograft tumours (FFPE) were stained for Ki67/phosphohistoneH3 (proliferation) and Masson's trichrome/anti-sma (Collagen/stroma). EGFR-MET interaction was assessed by co-immunoprecipitation and Forster resonance energy transfer (FRET) FLIM to quantify EGFR-MET dimers after SGX523 treatment. Results: SGX523 treatment significantly reduced H1975 xenograft tumour growth/weight. Proliferation was suppressed in vitro (BrdU %) and in vivo (phosphohistone-H3). Conversely in H1975 L858R, SGX523 reduced stroma (Masson's trichrome) and migration. EGFR-MET dimers were more common in H1975 than H1975 L858R/WT. This was associated with a mesenchymal, migratory phenotype in the H1975 cells whilst H1975 L858R were more proliferative. SGX523 reduced EGFR-MET dimerization (FRET %) in H1975 cells/FFPE xenograft tumours but induced dimer formation in H1975 L858R. H1975 WT showed little response to MET inhibition and low EGFR-MET FRET. In treated mice, FRET correlated with Ki67. Conclusions: MET therapy was most effective in H1975 suggesting greater MET dependence with EGFR L858R/T790M. EGFR L858R-T790M interacted most with Untreated MET. MET inhibition reduced EGFR-MET dimerization in H1975 but increased H1975-L858R FRET. EGFR-MET FRET assays can be applied to 'FFPE' processed lung cancer tissue from murine xenografts.